History of the Conservation Javanese-hawk Eagle (Nisaetus bartelsi) in Java Island 1993 - 2020 - Muhamad Satria Nugraha; Reiza D. Dienaputra (Universitas Negeri Semarang, 2026)
Based on Presidential Decree No. 4 of 1993, the Javanese-hawk eagle (Nisaetus bartelsi) is a national animal and is classified as an endangered species. The conservation of the Javanese eagle is experiencing dynamics both in terms of habitat and population. The Javanese-hawk eagle has a tendency to choose primary forest as its habitat. The existence of primary forests intersects with social life on the island of Java because primary forests are not always in line with human needs. The purpose of this study is to provide an explanation of the conservation of the Javanese-hawk eagle from 1993 to 2020. This research is intended to provide an overview of the preservation of Javanese-hawk eagles in the future by reflecting on their preservation in the past using historical methods consisting of heuristics, criticism, interpretation, and historiography. Javanese-hawk eagle conservation is found in several places such as Mount Gede Pangrango National Park, Alas Purwo National Park, and conservation areas around mountains in Java. The Javanese-hawk eagle population from 1993 to 2020 was dynamic due to habitat availability, preservation, and breeding period for the Javanese-hawk eagle. The preservation of the Javanese-hawk eagle requires awareness from various parties because it requires proper regulations and implementation. This research is expected to be a guide for the preservation of Javanese-hawk eagles in the future by reflecting on the perspective of the past.